Multidimensional Insider Threat Detection Model For Organization - Ganthan Narayana Samy; Nurazean Maarop; Bharanidharan Shanmugam; Mugilraj Radhakrishnan; Sundresan Perumal; Fiza Abdul Rahim (Little Lion Scientific, 2024)
Indexed by Scopus/ERA